Firm Size, Capital Intensity dan Inventory Intensity terhadap Agresivitas Pajak - Adibah Yahya; Eva Gandawati Agustin; Preatmi Nurastuti (Universitas Negeri Padang, 2022)
Tax aggressiveness is an action to manipulate the amount of taxable profit or to save tax costs that should be paid by the company. The factor that influences it is mainly cost, because the greater the company's costs through capital intensity and inventory intensity, it will reduce the tax burden. Aggressive actions tend to be carried out by large companies. The purpose of this study was to determine how much the impact of firm size, capital intensity and inventory intensity on tax aggressiveness. The research population is manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020 with a total sample of 134 research data. The method of analysis used multiple linear analysis. The results showed that simultaneously firm size, capital intensity and inventory intensity had an effect on tax aggressiveness. While partially firm size, capital intensity has no effect on tax aggressiveness, and inventory intensity has a positive effect on tax aggressiveness.